Comprehensive study on Heuristics approaches to solve multi objective problems - et. al, Dr. Jayachitra Selvaraj (International Journal of Advanced Science and Technology, 2020)
Heuristics approaches are population based and inspirited by biological or human intelligence phenomena.  In common, these approaches are associated with large scale problems and implemented to resolve linear, nonlinear, differential and non-differential problems. A wide variety of population-based techniques, such as Differential Evolution (DE), Genetic Algorithm (GA), Simulated Annealing (SA), Evolutionary Programming (EP), Tabu Search (TS), Biogeography Based Optimization (BBO), Artificial Bee Colony (ABC), Particle Swarm Optimization (PSO) and Gravitational Search Algorithm (GSA) are few optimization techniques based on population search to solve these problems. A detailed comprehensive study was carried out with respect to the following parameters: type of Flexible AC Transmission System (FACTS) device, objective function(s), benchmark system and optimization method was implemented.  This survey focused the directions for future research in the area of electrical engineering especially towards, allocation of FACTS device and its rating in power system network.